Jappy Tonny Introduction to Peircean Visual Semiotics - Cruz Moscoso, Franklin de la (Lenguas Modernas, 2013)
Bloomsburry Advances in Semiotics. Bloomsburry Academic, Bloomsburry Plublishing, London, New York. Kindle Edition 2013, 240 páginas ISBN: 978-1-4411-3289-5